KARAKTERISTIK JAMBAL ROTI IKAN MANYUNG (Arius thalassinus) DENGAN SUPLEMENTASI BAKTERI ASAM LAKTAT INDIGENOUS - Merkuria Karyantina Karyantina; Sri Anggrahini; Tyas Utami; Endang Sutriswati Rahayu (AGROINTEK, 2021)
Jambal roti is a fermented product of sea catfish (Arius thalassinus) with the manufacturing process uses a high salt concentration (30%), and is still done traditionally. High salt in fish processing causes consumers to hesitate in consuming the product. The fish fermentation process involves several bacteria, including lactic acid bacteria, which will break down fish protein into other compounds that affect the chemical and microbiological characteristics of the product. This study aims to analyze the effect of supplementation of the variation of salt content (20%, 25% and 30%) and the indegenous lactic acid bacteria  (control, Lactobacillus plantarum, Pediococcus acidilactici and Pediococcus pentosaceus) on the chemical and microbiological characteristics of the jambal roti. The results showed that the 25% salt content with Lactobacillus plantarum supplementation had the best characteristics among the other treatments, namely the number of coliform bacteria (2,11 log cfu / gram) and Salmonella-Shigella (2,18 log cfu / gram) the least among others treatments, total bacteria (7,26 log cfu/gram) and total lactic acid bacteria (4,58 log cfu/gram). Chemical characteristics includes moisture content 32,53%, ash content 23,08% wb, Aw 0,67, fat content 1,74% (w / b), NaCl content 18,10%  and total protein 35,11%..